The Design and Evaluation of a Decentralized E-Voting System Using Ethereum Smart Contracts - Ludgerdus Pati Hurit; Yo'el Pieter Sumihar; Haeni Budiati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The widespread implementation of electronic voting systems poses ongoing challenges related to data integrity, transparency, and centralized control, which can increase the risk of vote manipulation and reduce traceability. To address these issues, this study designs and evaluates a decentralized electronic voting system implemented using Ethereum smart contracts. The objective of this research is to test the ability of blockchain technology to support a secure, transparent, and tamper-resistant voting process in a decentralized environment. The research methodology includes requirements analysis, system design, system implementation, and functional testing. Black-box testing was conducted to verify the system's functionality throughout the voting process. The proposed system permanently records voting transactions on the blockchain, preventing unauthorized modifications while allowing transaction verification by network participants. Voter privacy is maintained by separating voter identity data from voting records and implementing blockchain address abstraction, ensuring that individual votes cannot be directly linked to voter identities. System evaluation focuses on transaction costs and confirmation times. Performance testing was conducted using six test transactions on the Sepolia blockchain network. The total transaction cost recorded was 0.006076 ETH, with an average cost of 0.001013 ETH per transaction. The minimum transaction cost of 0.000091 ETH occurred during voting operations, while the maximum cost of 0.005596 ETH was associated with smart contract deployment and higher network base fees. The average transaction confirmation time was approximately 12 seconds. Although the evaluation was based on a limited number of transactions, the results indicate that the proposed system demonstrates reliable transaction execution, acceptable gas usage, and high transparency. Further large-scale testing is recommended for future work.